(untitled) (Research, Society and Development, 2021)
Introduction: health Care-Related Infections are seen as an important health problem, as they result in high mortality, prolonged hospitalization, increased cost of care and favored the selection and dissemination of multi-resistant microorganisms. Objective: to describe the profile of microbial resistance of diseases related to health care in a hospital for infectious diseases in a capital of northeastern Brazil. Methods: descriptive, quantitative and retrospective observational study. Research carried out through data collection in the hospital infection control commission sector in the notification forms, culture tests and antimicrobial sensitivity test of patients who were hospitalized in the years 2018 and 2019 and developed infection during the hospitalization period. Results: 52 forms of notifications of infections related to health care were analyzed. Six infection sites were identified: lung (26.0), urinary tract (13.0), integument (6.0), trachea (3.0), intra-abdominal (2.0) and blood (2,0); with emphasis on the respiratory system: pulmonary diseases were observed in 50.0% of those desired. In our research, the highest frequency of resistance observed in the wards of ceftriaxone (11.0/84.6%), followed by sulfazotrim (5.0/83.3%) and ampicillin with sulbactam (8.0/80.0%) While in the Intensive Care Unit, the highest resistance profile was sulfazotrim (4.0/100%), followed by ampicillin with sulbactam (9.0/90.0%), piperacillin with sodium tazabactam (9.0/75.0%). Conclusion: the data presented show the frequency of multidrug resistance mainly in Gram-negative bacteria: Pseudomonas aeruginosa (8.0), followed by Acinetobacter baumannii (7.0), and Escherichia gergoviae (5.0).